Analisis Peran Strategis pada Sumber Daya Manusia dalam Mendukung Keberhasilan Pemasaran Digital - Ahmad Daenuri; Munawaroh Munawaroh (Pusat Riset dan Inovasi Nasional, 2025)
Digital transformation has changed the way companies do business, including in the marketing aspect which is now shifting to digital platforms as the main strategy. Digital marketing requires an approach that is not only technology-based, but also supported by competent and strategic human resources (HR). In the digital era, the need for special competencies such as data analytics, social media management, and interactive content design is becoming increasingly important. However, the challenges that are often faced include weak employee competencies, resistance to change, and limited budgets for training and skills development. To overcome these challenges, companies need to implement a proactive HR management strategy, including organizing ongoing training, implementing supporting technology, and establishing an innovative and adaptive work culture.